The health impacts of extractive industry transnational corporations: a study of Rio Tinto in Australia and Southern Africa - Julia Anaf; Frances Baum; Matt Fisher; Leslie London (BMC, 2019)
Abstract Background Operations of transnational corporations (TNCs) affect population health through production methods, shaping social determinants of health, or by influencing regulation of their activities. Research on community exposures to TNC practices and policies has been limited. Our research on extractive industries examined Rio Tinto in Australia and Southern Africa to test methods for assessing the health impacts of corporates in high and middle income jurisdictions with different regulatory frameworks. Methods We adapted existing Health Impact Assessment methods. Data identifying potential impacts were sourced through media analysis, document analysis, company literature and semi-structured interviews. The data were mapped against a corporate health impact assessment framework (CHIA) which included Rio Tinto's political and business practices; productions; and workforce, social, environmental and economic conditions. Results Both positive and detrimental aspects of Rio Tinto's operations were identified. Requirements imposed by Rio Tinto on its global supply chain are likely to have positive health impacts for workers. However, political lobbying and membership of representative organisations can influence government policy in ways that are unfavourable to health and equity. Positive impacts include provision of direct employment under decent working conditions, but countered by an increase in precariousness of employment. Commitments to upholding sustainable development principles are undermined by limited site remediation and other environmental impacts. Positive contributions are made to national and local economies but then undermined by business strategies that include tax minimisation. Conclusion Our study confirmed that it is possible to undertake a CHIA on an extractive industry TNC. The different methods provided sufficient information to understand the need to strengthen regulations that are conducive to health; the opportunity for Rio Tinto to extend corporate responsibility initiatives and support their social licence to operate; and for civil society actors to inform their advocacy towards improving health and equity outcomes from TNC operations.